Symptom control analysis of patients in a palliative care unit - Martins, Conceição (2016)
ABSTRACT Background: In order to improve the quality of life of the patient and family it is essential to control symptoms, not only the physical ones, but also the psychological, social and spiritual. Objectives: To characterize the symptoms manifested by patients admitted to a palliative care unit and analyze the evolution of the symptoms of patients admitted to the palliative care unit (PCU) in the northeastern region of Portugal between 2009 and 2014. Methods: A quantitative, descriptive and retrospective study. Data collected through the care records and evaluation of the patient RNCCI [National Network of Integrated Continuous Care Units]. Statistical data were treated through Microsoft Excel and SPSS version 22.0 for Windows. The study encompasses the patient characterization data, the source, causes for requesting the diagnosis, assessment of the risk of falling according to the Morse scale, risk of pressure sores according to the Braden scale, the palliative care scale, symptom assessment according to Edmonton and pain assessment. Results: The patients were mostly male with a mean age of 73.5 years (± 11.4 years), married, retired and with under 6 years of schooling. The referral of patients is predominantly by the hospital and the diagnoses are mostly oncological. The number inpatient days were found to be 32.5 days on average and 83.7% of patients died in the PCU. Most patients have a high risk of falling and a high risk of pressure sores. In the palliative care scale and Edmonton symptom assessment the symptoms were found to be controlled in most patients. Conclusion: It was possible to observe that there is symptom control which is an asset for the quality of end of life of hospitalized patients and an improvement for the delivery of palliative care.